Predicted kinetic behaviour of the oxidative degradation of organic pollutant using substituted MeCuFeO3 (Me = Ca, Sr, CaSr) perovskite catalysts / Rasyidah Alrozi ... [et al.] - Alrozi, Rasyidah; Zubir, Nor Aida; Abu Bakar, Noor Fitrah; Motuzas, Julius; Abu Bakar, Noor Hana Hanif Abu Bakar; Wang, David (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
The substitution of different types of A-site metal cations within the perovskite structure leads to a change in the catalytic activity of the resultant catalyst, which subsequently affects the overall kinetic behaviour of the degradation of organic pollutants. Hence, understanding the kinetics behaviour of the substituted perovskite catalysis is crucial for determining the reaction rates of the degradation process. This study investigates the catalytic performance and kinetic analysis of substituted MeCuFeO3 (Me = Ca, Sr, CaSr) perovskite catalysts in the oxidation of organic pollutants, namely acid orange II (AOII) dye. The highest AOII degradation was achieved by CaCuFeO3 (97 %) followed by CaSrCuFeO3 (95 %) and SrCuFeO3 (91 %) within 60 min of reaction in the presence of oxidant (H2O2). Interestingly, the AOII oxidation by CaCuFeO3 followed a pseudo-second-order kinetic model while SrCuFeO3 and CaSrCuFeO3 were fitted to the BMG kinetic model. The reaction rate constant of CaCuFeO3 (k = 1.9 × 10−2 L.mg−1.min−1) was higher by a magnitude of two and three than that of CaSrCuFeO3 (k = 9.4 × 10−3 L.mg−1.min−1) and SrCuFeO3 (k = 6.3 ×10−3 L.mg−1.min−1), respectively. These results indicate that the partial substitution of Sr in the A-site of CaCuFeO3 leads to a slight deterioration in the overall catalytic performance of the oxidative degradation of AOII, which contributes to a change in the behaviour of the reaction kinetic models.